ROLE OF MASS MEDIA IN BUSINESS COMMUNICATION - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages; Xamidov Iskandar, Ubaydullayeva Ro’zixon, Toshtemirova Erkinoy the student of Andijan State Institute of Foreign Languages, 312-group – English language; literature (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
This article about, the purpose of mass communication is to spread a message and to reach a large and diverse audience. In the business world, mass communication is a term that refers to communicating in a way that reaches and affects a large amount of people in a short amount of time. Companies may use mass communication in order to announce a new product, reach a target market, send a message, or any number of other reasons.